A rock-cut burial cave from the Roman Period at Beit Nattif, Judean foothills - Ziso, Boʿaz (Israel exploration journal, 2011)
This article presents a tomb excavated in 1945 at Beit Nattif in the Judaean foothills and discusses it in light of the history and archaeology of the site. The burial chamber was initially a rock-cut water cistern, and at a later date, the cistern was converted into a burial chamber with kokhim. The tomb was used during the first and third–fourth centuries CE, as attested by the typical oil lamps, pottery and inscriptions. Three distinct phases were observed: in the first, a water cistern was cut in the bedrock and its side walls were covered with plaster. Probably in the late first century BCE or the early first century CE, the cistern was converted into a burial chamber. The pottery and the oil lamps represent two different phases (2 and 3) of use of the former cistern for burial. At first, during the Early Roman period (phase 2), 12 kokhim and three arcosolia were hewn into the walls of the cistern. In this period the burial cave was probably still used by Jews, residents of Pella/Betholetepha — the capital of the Judaean toparchy. During the Late Roman period (phase 3), the chamber was reused by non-Jews for burial purposes. Names were incised on the plaster walls in this phase, and most of the oil lamps also belong to this phase. Beit Nattif was still an important site in the Late Roman period. The place was now inhabited by Roman citizens and veterans, who settled the region as part of the Romanisation process that took place in the rural areas of Judaea after the Bar Kokhba war.